Orientasi Politik Pemilih Perempuan pada Pemilu Tahun 2019 di Kabupaten Kepulauan Seribu Provinsi DKI Jakarta - Ikatrina Rosyidah; Sri Budi Eko Wardani (Jurnal Syntax Admiration, 2024)
The purpose of this study is to explain the extent of the influence of socioeconomic status and political participation on the political orientation of women voters in the 2019 General Election in the Thousand Islands Regency, DKI Jakarta Province. The method used in this study is a quantitative approach, namely with one of the characteristics commonly found in quantitative research with causality, which tries to explain the question "why" to examine the cause of an empirical event or phenomenon. The results showed that employment, involvement in community organizations, and participation in elections partially had a significant effect on the political orientation of women voters, while income, education, and involvement in political parties did not. These findings highlight the importance of considering the various aspects that affect voter participation in each region, although the study also highlights limitations, such as the geographical characteristics of the archipelago and weather factors that affect data collection